Sources And Patterns Of Spelling Errors In Language-Learners Language : An Investigation Of Persian Learners Of English - Solati, Akhbar (2011)
This study investigates the sources and patterns of spelling errors of Persian English language learners. There are four major objectives. First, it attempts to determine sources of interlingual errors in the spelling of Persian English language learners. Next, it endeavors to determine sources of intralingual errors in the spelling of Persian English language learners. Then, this study will establish patterns of interlingual errors in the spelling of Persian English language learners. And finally, it will establish patterns of intralingual errors in the spelling of Persian English language learners. Forty Persian English language learners participated in this study. They have been randomly selected from the total population of 200 Persian English language learners who are studying in grade one of secondary education cycle in Daragaz, a city in Khorasan Razavi state of Iran. The data was gathered using a word dictation test. To achieve the objectives, the procedures utilized in this study for identification of spelling errors were adopted from Corder (1974).